Reviving Christian humanism : the new conversation on spirituality, theology, and psychology - Browning, Don S. (Theology and the sciences., 2010)
"Browning argues that the time is right for religious intellectuals in conversation with the social sciences to reinvigorate the deep humanistic strands of the grand religions and enter into global interfaith dialogue on that basis. Concentrating on the Christian heritage, he draws on such diverse disciplines to envision a broader canvas for psychology, a keener theological use of new insights from psychology, a more complex understanding of how personal change is fostered, a recognition of the indispensable role of institutions in personal formation and ethical deliberation, and in the end, a deeper spirituality that directly feeds the common human endeavor and the public good."--Publisher's description